A hybrid algorithm of interval type-2 fuzzy logic system and generalized adaptive resonance theory for medical data classification - Leow S.Y.; Wong S.Y.; Yap K.S.; Yap H.J. (IOS Press, 2023)
Arts computing; Classification (of information); Computer aided diagnosis; Computer circuits; Diagnosis; Diseases; Functional polymers; Fuzzy inference; Neural networks; Resonance; Uncertainty analysis; Adaptive resonance theory; Adaptive resonance theory networks; Classification tasks; Generalized Regression Neural Network(GRNN); Interval type-2 fuzzy logic systems; Model uncertainties; Regression problem; Type 2 fuzzy sets (T2 FS); Fuzzy logic